Analisis Sifat Fisik dan Kimia Yogurt Yang Menggunakan Starter Lactobacillus bulgaricus Dengan Persentase Yang Berbeda - Yusdar Zakaria (Jurnal Agripet, 2001)
ABSTRACT. A study of pyisical properties and quality of yogurt with Lactobacillus bulgaricus as a starter has been doon. Objectives of this study is to know how many percent starter of L. bulgaricus in yogurt to decrease suscepetibility to syneresis and to increase quality of yogurt. Yogurt was analyzed for susceptibility to syineresis, titratable acidity and content of crude protein and crude fat. Syinerisis of yogurt was evaluated according to centrifugal methods of Halwarkar and Kalab. The result of the study showed that yogurt with 2.5-10 % L. bulgaricus as a starter are not have any effect of susceptibility to synerisis and content of crude fat, but centripuged at 250-1000 rpm. Had significantly different (0.01) on susceptibility to synerisis. On the other hand the increasing of centrifuge rotation, increase susceptibility to synerisis. The starter of 5-10% L. bulgaricus used in yogurt able to increase titratable acidity and content of crude protein. The yogurt prepared by 10% L. bulgaricus had the highest score (3.88%) of crude protein, although there is no significant differences with yogurt using 7.5% L. bulgaricus.